Impacto de la ecografía focalizada en toma de decisiones clínicas en la unidad de shock-trauma del Hospital Regional de Loreto 2023 - Rengifo Fernandini, Jose Carlos (2023)
Objective: To describe and demonstrate the impact of emergency focused ultrasound on clinical decision making in patients admitted to the shock-trauma unit of the Regional Hospital of Loreto, during the year 2023. Methodology: Cross-sectional Observational Study that will be carried out in the Shock-trauma unit of the emergency service of the Regional Hospital of Loreto. The population universe will be made up of all patients admitted to the Shock-trauma unit of the Loreto Regional Hospital from January 1 to December 31, 2023. The sample will consist of a total of 176 patients. To determine the relationship between the variables, the Chi2 test with statistical significance (p< 0.05) will be used. Conclusion: this study is applicable in the Shock-trauma unit of the Regional Hospital of Loreto, it will demonstrate the impact of focused emergency ultrasound (POCUS) in the best decision-making in patients admitted to said service.